Design of organic crystals with lone pairs to study spin resonance and spin-lattice interactions - Shilin Li; Xiangqian Lu; Wei Qin (NPG Asia Materials)
Abstract Lone pairs are widely prevalent in various types of molecules and have a significant impact on the band structure, carrier transport, and dielectric response, which are the key factors for exploring the underlying mechanism of phenomena in opto-spintronics. In this work, nitrogen substitutions with nonequivalent hybridization are adopted to obtain different types of organic charge transfer crystals, where lone pairs are generated to weaken the interactions between donors and acceptors, resulting in a blueshift in photoluminescence and a weaker electron-lattice coupling. Moreover, lone pairs could further strengthen the ability to transfer energy and spin angular momentum to the lattice vibration to enhance spin resonance. Additionally, due to the effect of lone pairs, the spin density inside the crystals is redistributed to tune the transition between the singlet and triplet states. Overall, crystals with lone pairs demonstrate a more diverse set of magnetic, optical, and spin-related properties.